Molecular Imprint for Electrochemical Detection of Streptomycin Residues Using Enzyme Signal Amplification. Issue 2 (22nd January 2013) - Que, Xiaohua; Liu, Bingqian; Fu, Libing; Zhuang, Junyang; Chen, Guonan; Tang, Dianping
Abstract We have designed a new molecularly imprinted co‐polymer (MIP) for the sensitive detection of streptomycin (STR) in food using enzymes as signal amplification. The MIP was fabricated via co‐polymerization of aniline and o‐phenylenediamine on gold substrate in the presence of STR as template. The assay is based on competitive binding of free STR and glucose oxidase‐labeled STR (GOx‐STR) to the imprinters on the MIP. On addition of glucose, hydrogen peroxide is formed that is detected by differential pulse voltammetry. Under optimal conditions, the decrease of the catalytic current is proportional to the STR concentration in the range from 0.01 to 10 ng mL−1, with a detection limit (LOD) of 7.0 pg mL−1 STR (at 3sB). Intra‐ and inter‐assay coefficients of variation (CVs) are<10.5 %. The system was further validated and evaluated with STR‐spiked samples including honey and milk, and the recovery was between 82 and 124.2 %.